Can digital transformation promote enterprise performance? From the perspective of public policy and innovation - Yongzhang Peng; Changqi Tao (Journal of Innovation & Knowledge (JIK), 2022)
As a new enterprise development model, digitization is of great significance to the development of economy and society. Using the data of relevant listed companies from 2012 to 2020, the panel measurement model is used to investigate the relationship between digital transformation and enterprise performance to further reveal the internal law of whether digital transformation helps to stimulate innovation momentum. The results show that digital transformation has greatly improved the performance of enterprises, and it can stimulate the momentum of enterprise innovation. Reducing costs, increasing revenue, improving efficiency, and encouraging innovation are the main paths for digital transformation to enable the development of enterprises, among which the policy effect of enterprise innovation is the most significant. This research is of great significance to improve the user demand orientation of enterprise innovation and research and development, as well as to realize the high-quality innovation and development of enterprises.
Keywords: O25; O32; 650; Innovation; Digital transformation; Enterprise performance; Public policy